An Integrated Approach of Video Game Therapy®: A Case Study - Maura Crepaldi; Francesco Bocci; Marcello Sarini; Andrea Greco (Information)
International literature in the field of rehabilitation and psychological support is increasingly characterized by the inclusion and use of video games and virtual media, even if the results are controversial. The theoretical basis on which the study presented is based is Video Game Therapy®. This approach uses commercial video games, which are generally free or available at a relatively low cost. These games possess many essential functions that make them practical as preventive tools or support for integration into traditional therapies. Video Game Therapy® allows the patient to reflect on emotional containment and cognitive self-regulation to establish a state of mental balance and well-being. It encourages insight and leads the player to reflect on some salient aspects of their character and lifestyle and their emotions and thoughts linked to specific life episodes relived in the game setting. Starting from these premises, the study shows promising results, presenting a single case of a boy with social isolation problems and relational difficulties, in which significant changes were highlighted in the perception, expression, and management of emotions, as well as in metacognition and self-efficacy.